2021
DOI: 10.1007/s12602-021-09789-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Safety of Lactobacillus casei IMV B-7280 Probiotic Strain on a Mouse Model

Abstract: Probiotics, in particular Lactobacillus (lactic acid bacteria, LAB) strains, are widely used in clinical practice. Despite that these probiotics have GRAS (generally regarded as safe) and qualified presumption of safety (QPS) statuses, the safety of particular strains still needs to be thoroughly studied. The aim of the study was to evaluate the safety of Lact. casei IMV B-7280 strain by investigating toxicity and the effects on gut microbiota in experimental anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In the other groups, the renal tubular epithelial cells of the mice were neatly arranged, the renal capsule was normal, and the renal corpuscle was uniform in texture. However, they evoked mild interstitial edema, which may be reversible [53]. Overall, histological studies in mice showed no abnormal or histopathological changes in tissues and organs.…”
Section: Biosafety Evaluation In Micementioning
confidence: 88%
“…In the other groups, the renal tubular epithelial cells of the mice were neatly arranged, the renal capsule was normal, and the renal corpuscle was uniform in texture. However, they evoked mild interstitial edema, which may be reversible [53]. Overall, histological studies in mice showed no abnormal or histopathological changes in tissues and organs.…”
Section: Biosafety Evaluation In Micementioning
confidence: 88%
“…Male BALB rats were orally dosed with L. casei IMVB-7280 at 5 × 10 6 , 5 × 10 8 , 5 × 10 9 CFU/day for 7 days or 1 × 10 10 CFU/day for 3 days, and a follow-up of 14 days. The survival rate of all mice was 100 %, and the weight remained unchanged [ 16 ]. The strain L. acidophilus was tested for its function against 1,2-dimethylhydrazine (DMH) and sodium dextran sulfate (DSS)-induced colon cancer in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were maintained in standard laboratory conditions (temperature 20–25 °C, humidity 50–60%, and 12 h light–dark cycle). Mice were randomly allocated to five groups: normal (N), cyclophosphamide (CPA) (CPA, Sigma-Aldrich Co.), red ginseng positive control (PC), and KBL346 at low (10 8 CFU/kg) and high (10 10 CFU/kg) dosages, as described previously with some modification [ 35 , 36 , 37 , 38 ]. The total duration of the animal experiment was 20 days.…”
Section: Methodsmentioning
confidence: 99%